Antimicrobial and autophototoxic effects of norharmane in termites - Siderhurst, Matthew Samuel, author; Bjostad, Louis B., advisor; Hegedus, Louis, committee member; Kondratieff, Boris C., committee member; Norton, Andrew, committee member (Colorado State University. Libraries, 2004)
The fluorescent alkaloid norharmane has been isolated from Reticulitermes termites and characterized by microcoil 1H NMR, UV/Vis, mass spectrometry and GC/MS. This is the first report of norharmane in insects, which is the major component in termite fluorescence under ultraviolet light. Norharmane was uniformly present at approximately 1 ng/mg in Reticulitermes tibialis Banks workers, soldiers and alates, R. flavipes (Kollar) workers and R. virginicus (Banks) workers. Some termites were observed to fluoresce with less intensity, but no differences in norharmane levels were detected. Norharmane occurs mainly in the termite hemolymph, and GC/MS analyses of metabolites from cultured Reticulitermes endosymbionts demonstrated that microorganisms are a biosynthetic origin of norharmane in termites. Norharmane shows antimicrobial activity at ecologically relevant concentrations against the entomopathogenic fungus Metarhizium anisopliae (Metschnikoff). Subterranean termites contend with substantial microbial disease pressure due to their soil habitat and social behavior, and norharmane may be a critical defense in countering this pressure. A quantitative survey of 18 termite genera, Anoplotermes, Amitermes, Cryptotermes, Coptotermes, Gnathamitermes, Heterotermes, Incisitermes, Kalotermes, Marginitermes, Microcerotermes, Nasutitermes, Neotermes, Paraneotermes, Prorhinotermes, Pterotermes, Reticulitermes, Tenuirostritermes and Zootermopsis, from the four largest Isopteran families, showed universal norharmane presence. Norharmane is therefore the most widespread antimicrobial defense yet reported, both across castes and phylogenetically. Norharmane was absent from five closely related taxa that were also analyzed. Norharmane is a phototoxic compound, and ultraviolet light exposure (30 and 60 W/m2) caused high autophototoxic mortality in Reticulitermes termites, suggesting novel pest control possibilities. Saprophagous Tyrophagus sp. mites associated with laboratory colonies of Reticulitermes were shown to besome fluorescent after ingesting norharmane from termite cadavers, but the mites showed no mortality when exposed to UV light. No UV-mediated mortality was observed in pavement ants, Tetramorium caespitum L., fed on sucrose and norharmane. UV exposure bioassays with half-covered arenas showed that Reticulitermes termites are negatively phototactic to ultraviolet light. Autophototoxicity was significantly reduced in half-covered arenas compared to uncovered controls.
Keywords: entomology; organic chemistry